Physical mapping of EPSPS gene copies in glyphosate resistant Italian ryegrass (Lolium perenne ssp. multiflorum) - Putta, Karthik (Kansas State University, 2017)
Italian ryegrass (Lolium perenne L. ssp. multiflorum (Lam.) Husnot), one of the problem weeds of the US, evolved resistance to multiple herbicides including glyphosate due to selection in Arkansas (AR). Glyphosate is a 5-enolpyruvylshikimate-3-phosphate synthase (EPSPS) inhibitor and amplification of EPSPS gene, the molecular target of glyphosate confers resistance to this herbicide in several weed species, including Italian ryegrass from AR. The objective of this study was to determine the expression of EPSPS gene and protein as well as distribution of EPSPS copies on the genome of glyphosate-resistant Italian ryegrass (ARR) using a known susceptible Italian ryegrass (ARS) from AR. EPSPS gene copies and expression of ARR and ARS were determined using quantitative PCR with appropriate endogenous controls. EPSPS protein expression was determined using Western blot analysis. Fluorescence in situ hybridization (FISH) was performed on somatic metaphase chromosomes to determine the location of EPSPS copies. Based on qPCR analysis, ARR plants showed a wide range of 12 to 118 EPSPS copies compared to a single copy in ARS. EPSPS gene expression correlated with the gene copy number in both ARR and ARS. Individuals with high EPSPS copies showed high protein expression in Western blot analysis. FISH analysis showed presence of brighter EPSPS signals, distributed randomly throughout the genome of ARR individuals compared to a faint signal in ARS plants. Random distribution of EPSPS copies was previously reported in glyphosate-resistant Palmer amaranth. Overall, the results of this study will help understand the origin and mechanism of EPSPS gene amplification in Italian ryegrass.
Keywords: Glyphosate resistant Italian ryegrass; Herbicide resistance; Physical mapping of EPSPS gene; Lolium multiflorum; Glyphosate resistance; Gene amplification